Pengaruh Risiko Kredit dan Likuiditas terhadap Kecukupan Modal pada Bank Syariah yang Tercatat Di BEI - Edi Kurniawan; Nafisah Nurulrahmatia; Puji Muniarty (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
Credit risk is a risk that occurs due to the failure of customers or other parties to fulfill their obligations to the bank. Credit risk is the risk of possible losses as a result of non-repayment of credit provided by the bank to debtors (Natasia 2014). The higher the credit risk of a bank, the greater the number of problem loans. Credit risk can be measured by the Non Performing Financing (NPF) ratio. Nugraha 2018) Non Performing Financing or commonly abbreviated as NPF is the ratio between problematic financing and total financing disbursed by sharia banks. Nuha (2016) Non Performing Financing (NPF) is a comparison of problematic credit/financing with the total credit/financing provided. The higher the NPF ratio indicates a bank's inability to manage its problematic credit/financing, this will reduce the level of confidence of a bank in carrying out business activities. Problematic financing consists of substandard, doubtful and non-performing financing.